Exploiting the photocatalytic activity of TiO2 towards the depolymerization of Kraft lignin. (4th August 2021) - Crites, Charles-Oneil L.; Gomes de Mendonça, Fernanda; Netto-Ferreira, José Carlos; Baker, R. Tom; Hallett-Tapley, Geniece L.; Tremblay, Luc
Abstract : Lignin is a promising renewable source of aromatic chemicals. Abstract : Lignin is a promising renewable source of aromatic chemicals. Described herein is a new photocatalytic methodology for depolymerization of oxidized Kraft lignin to industrially relevant aromatic platform chemicals. The photooxidation route begins with oxidation of alcohol moieties using a gold nanoparticle/hydrotalcite composite. Next, the oxidized lignin is subjected to UVA irradiation in the presence of TiO2, leading to a 3-fold decrease of its molecular weight and to the formation of various monolignols. The products obtained in both steps were characterized using FTIR, SEC, GC-MS, and 2D NMR spectroscopy, which confirm the depolymerization of lignin to smaller molecular weight products. This method offers both energetic and chemical advantages over thermochemical processing for lignin valorisation.